다중 초음파 조사 반응조에서의 TCE의 초음파 분해 - 이민주(Min Ju Lee); 오재일(Je Ill Oh) (Daehan hwan'gyeong gonghag hoeji, 2009)
Sonolysis of TCE (Trichloroethylene) was performed in 584 kHz rectangular reactor. At first, the effect of acoustic power and aqueous temperature which are both important factors to operate ultrasound system on sonolysis of TCE were examined under one side irradiation condition. First degradation rate constants of TCE and chloride yields were increased with increasing acoustic power from 100 to 300 W. And increasing the aqeuous temperature resulted in the increase of first degradation rate constants of TCE and the decrease of chloride yield. Sonolysis of TCE was performed under multi ultrasound irradiation conditions that total acoustic power of 300 W was distributed according to the number of irradiation sides. First degradation rate constants of TCE followed the order 4 sides > 3 sides > 1 side > 2 sides (parallel) > 2 sides (orthogonal). When comparing the experimental results under parallel and orthogonal irradiation conditions of 2 sides with 300 and 450 W, first degradation rate constants of TCE were similar, while production rate constants of hydrogen peroxide were more higher at parallel conditions compared to orthogonal conditions. 584 kHz 정사각형 Batch형 초음파 반응조를 이용하여 TCE (Trichloroethylene)의 초음파 분해에 대한 연구를 수행하였다. 단면 조사 조건에서 초음파 시스템에서의 중요한 운전인자인 초음파 출력과 수용액 온도 조건의 영향에 대한 기초 연구를 수행하였으며, 다중 조사 조건에서의 초음파 출력 분배와 조사각에 따른 초음파 효과에 대해 고찰함으로써 제작된 반응조의 처리 효율을 검증하였다. 단면 조사 조건에서 초음파의 출력을 100에서 300 W로 단계적으로 증가시킬 때 TCE의 분해 속도 상수와 $H_2O_2$의 발생 속도 상수, 그리고 TCE의 무해화(mineralization) 정도의 판단 지표인 chloride의 발생 또한 모두 함께 증가하였다. 한편 초음파 출력 200 W 조건에서 수용액의 온도를 10에서 $30^{°}C$로 증가시킴에 따라 TCE 저감 속도 상수와 $H_2O_2$ 발생 속도 상수는 증가한 반면, chloride 발생은 오히려 감소하였다. 다중 조사 조건에 대한 실험 결과 300 W의 초음파 출력을 1, 2(직각), 2(정면), 3, 그리고 4면의 조사면에 따라 분배하였을 때 TCE의 분해 속도 상수는 4면 > 3면 > 단면 > 2면 정면 > 2면 직각의 순으로 조사면 수가 많아질수록 다소 증가하는 경향을 나타내었다. 그러나 최대, 최소값의 큰 차이는 나타나지 않았다. 300 W와 450 W의 출력 조건에서 2면 정면과 직각 분배 조건에 대한 실험 결과를 비교한 결과 TCE의 분해 속도 상수는 거의 비슷하였으나 $H_2O_2$는 2면 정면 조건에서 더욱 많이 발생하는 것으로 나타났다.